К новейшему решению индоевропейской проблемы - Лeлeков, Л. A.
Lelekov, L.A., On the Latest Solution of the Indo-European Problem; engl. Résumé; zu Gamkrelidze-Ivanov, NAA 1980, 64 ff. und VDI 3/1980, 3 ff.